Maximal oxygen uptake changes during judoist`s periodization training - Almansba, R.; Sterkowicz, S.; Sterkowicz-Przybycien, K.; Belkacem, R. (Archives of Budo, 2010)
Background and study aims: to evaluate the maximal oxygen uptake (VO 2max) of judoists in consecutive training periods: a) GPP, b) SPP, c) CP. Material and methods: Fifteen male judoists aged of 22 ± 7 years took part in this study. Their competition levels varied from departmental (group D, n = 7) to inter-regional (group IR, n = 8) experience. The standing height was measured with a wall-mounted wooden stadiometer. An electronic weighing scale was used to assess the body mass (W) in each period of preparation. The VO2max was measured indirectly using the multistage 20- meters shuttle run test. Results: The performance level had a statistically significant bearing (p<0.001) of judo competitors weight, but not with the time factor. The pattern of changes in weight in both groups IR and D was different during the training period. We also noticed that the weight of group D members decreased in SP period and increased in CP. We didn`t observed a significant difference of VO2max between group D and IR (95% Tukey HSD intervals are overlapping). The competition level affects significantly the HRmax (p<0.001). Group D presented higher HRmax values in three testing periods (GPP, SP and CP) than IR group. The time factor was close to reach significance level. Conclusion: The VO2max of judoists varies in consecutive training periods. The HRmax is correlated to the sport level but it less sensitive at workload variations than the HRmax. A moderate aerobic state doesn`t suggest a low judo performance. Tests more specifically linked to judo could be proposed to provide more information about this aspect.